2020
DOI: 10.1063/5.0009853
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing tilt effects on wind plants

Abstract: Tilting the nacelle of a wind turbine modifies entrainment into the wind plant and impacts total efficiency. Wakes are deflected vertically by tilt and in the case of large angles can disrupt entertainment from the undisturbed flow or dissipate on the ground. The effect of nacelle tilt on wake behavior is investigated in a series of wind tunnel experiments for the first time. Scale model turbines with a hub height and a diameter of 12 cm are arranged in a Cartesian array composed of four rows of three turbines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 39 publications
4
33
0
Order By: Relevance
“…Unless a downwind rotor is used or the tower design is corrected, it is almost inevitable that the rotor will be slightly lowered by forwards tilting. It should also be recognized that tower interactions can change for positive and negative tilt (Santoni et al 2017;Scott et al 2020a). However, in this study the tower is tilted with the rotor, thereby keeping the tower-blade distance constant, such that a minimal impact on performance is expected.…”
Section: Available Powermentioning
confidence: 96%
See 2 more Smart Citations
“…Unless a downwind rotor is used or the tower design is corrected, it is almost inevitable that the rotor will be slightly lowered by forwards tilting. It should also be recognized that tower interactions can change for positive and negative tilt (Santoni et al 2017;Scott et al 2020a). However, in this study the tower is tilted with the rotor, thereby keeping the tower-blade distance constant, such that a minimal impact on performance is expected.…”
Section: Available Powermentioning
confidence: 96%
“…For negative tilt, the wake is directed towards the ground such that it is affected by blockage of the ground, and interacts with lower-momentum flow with a higher level of turbulence. This downwards displacement aids in directing high-momentum flow from above the turbine to the rotor region of the next turbine, thus enhancing downwards transfer of kinetic energy (Scott et al 2020a); a relevant quantity as indicated by Calaf et al (2010) and Cal et al (2010). As a result, the wake shape spreads wider as it is pushed into the ground.…”
Section: Wake Shapementioning
confidence: 99%
See 1 more Smart Citation
“…In addition to yaw control, where wakes are deflected horizontally, it has been more recently proposed to deflect wakes in the vertical direction by acting on the rotor-tilt angle (see e.g. Guntur et al, 2012;Fleming et al, 2014Fleming et al, , 2015Annoni et al, 2017;Bay et al, 2019;Cossu, 2020;Scott et al, 2020;Nanos et al, 2020). Best performances are obtained for positive tilt angles, where the wake is deflected towards the ground (or the sea surface).…”
mentioning
confidence: 99%
“…Global power gains are achievable also for tilt control despite the power losses experienced by tilted-rotors upstream turbines (Fleming et al, 2015;Annoni et al, 2017;Bay et al, 2019;Cossu, 2020;Scott et al, 2020;Nanos et al, 2020). In a companion paper (Cossu, 2020, referred to as C2020 in the following), we have recently shown that by tilting upstream rotors of spanwiseperiodic turbine rows, turbine wakes (low-speed fluid) can be replaced with high-speed streaks, i.e.…”
mentioning
confidence: 99%